2014
DOI: 10.1556/aalim.43.2014.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Antibrowning and antimicrobial effects of onion essential oil to preserve the quality of cut potatoes

Abstract: This study evaluated the effect of onion essential oil (OEO) (0, 0.5, 2.5, and 5 mg ml -1 ) on microbial growth, browning decay, and sensorial appealing of cut potatoes stored for 15 days at 4 °C. Dipropyl disulphide and dipropyl trisulphide were the main constituents identified in OEO, and its application at a dose of 0.5 mg ml -1 was the most effective to prevent browning (38.5% inhibition respect to control) during storage, inhibiting PPO activity (39% respect to control) after the treatment. The higher the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…In another study, the application of onion EO (0.5–5 mg/ml) on fresh‐cut potatoes was effective to prevent enzymatic browning, inhibit PPO activity, and reduce microbial growth. Also, odor and flavor appealing of treated potatoes were well received by a sensory panel after 10 days (Vazquez‐Armenta, Ayala‐Zavala, Olivas, Molina‐Corral, & Silva‐Espinoza, ). Furthermore, edible pectin coatings enriched with cinnamon leaf oil (7.3–36.1 mg/ml) were applied on fresh‐cut peaches and positively affected odor acceptability; also, some consumers proposed that it could be used in a salad mixture or as a dessert ingredient (Ayala‐Zavala et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the application of onion EO (0.5–5 mg/ml) on fresh‐cut potatoes was effective to prevent enzymatic browning, inhibit PPO activity, and reduce microbial growth. Also, odor and flavor appealing of treated potatoes were well received by a sensory panel after 10 days (Vazquez‐Armenta, Ayala‐Zavala, Olivas, Molina‐Corral, & Silva‐Espinoza, ). Furthermore, edible pectin coatings enriched with cinnamon leaf oil (7.3–36.1 mg/ml) were applied on fresh‐cut peaches and positively affected odor acceptability; also, some consumers proposed that it could be used in a salad mixture or as a dessert ingredient (Ayala‐Zavala et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported lowest acceptability in fresh‐cut tomatoes treated with 0.001 and 0.002 g kg −1 garlic EO; only control tomatoes and those treated with 0.0005 g kg −1 garlic EO were acceptable . Additionally, application of onion EO on potatoes slices improved their odor and flavor acceptability after 10 days of storage, when only a small amount of sulfur compounds on slices was detected . Therefore it is necessary to find effective concentrations of compounds exhibiting high antibacterial activity without affecting the sensory quality of foods.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of fresh‐cut tomato slices to garlic EO volatiles in food‐grade polystyrene containers reduced microbial growth, but high concentrations (0.001 and 0.002 g kg −1 ) reduced acceptability; only control tomatoes and those treated with a low dose (0.0005 g kg −1 ) of garlic EO remained acceptable . In another study, onion EO applied to potatoes slices was effective in reducing microbial growth, but flavor acceptability was negatively affected at 5 g L −1 with respect to lower concentrations (0.5, 2.5 and 0 g L −1 ) . For this reason, it is necessary to optimize the application of EOs as food antibacterial agents, reducing sensory impact and maintaining/improving antibacterial efficacy.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations